Approximation of solutions to the optimal control problems for systems with maximum - Dashkovskiy, S.; Kichmarenko, O.; Sapozhnikova, K. (Нелінійні коливання, 2018)
We consider optimal control problems for nonlinear systems which dynamics depends on the maximum of the control function and the maximum of the state over some prehistory time interval. We are
interested in approximation of solutions for such kind of problems. Averaging method is developed for
this purpose. Розглянуто задачi оптимального керування нелiнiйними системами, динамiка яких залежить вiд
максимуму функцiї керування та максимуму стану на деякому часовому iнтервалi передiсторiї.
Дослiджено апроксимацiю розв’язкiв таких задач. З цiєю метою обґрунтовано метод усереднення.